Calculation Method and Influence Factors Analysis of Pressure Angle of Hole- pin Type Few Teeth Difference Planet Gear Speed Increaser - Wang Kaijie; Suo Shuangfu; Yang Yiyong (Jixie chuandong)
In view of the operating principles and structural characteristics of hole-pin type few teeth difference planet gear speed increaser,the contacting conditions of pin and pin hole during the operating process for various structure parameters are analyzed. Based on the geometrical relationship during operating process,the pressure angle analytic formula between pin and pin hole is derived. The curve of pressure angle is calculated and drawn by selecting different design parameters to find the relationships of pressure angle with rotor eccentricity,the turning radius of pin hole,diameter of pin and pin hole. The calculation methods and analytical results could guide the structure design of hole-pin type few teeth difference planet-gear speed increaser,optimization of the system force transmission characteristic.